90-Day readmission after radical prostatectomy—a prospective comparison between robot-assisted and open surgery. (2nd January 2019) - Wallerstedt Lantz, Anna; Stranne, Johan; Tyritzis, Stavros I.; Bock, David; Wallin, David; Nilsson, Hanna; Carlsson, Stefan; Thorsteinsdottir, Thordis; Gustafsson, Ove; Hugosson, Jonas; Bjartell, Anders; Wiklund, Peter; et al.
Abstract: Purpose: All types of surgery are associated with complications. The debate is ongoing whether robot-assisted radical prostatectomy can lower this risk compared to open surgery. The objective of the present study was to evaluate post-operative adverse events leading to readmissions, using clinical records to classify these adverse events systematically. Materials and methods: A prospective controlled trial of men who underwent robot-assisted laparoscopic (RALP) or retropubic radical prostatectomy (RRP) at 14 departments of Urology (LAPPRO) between 2008 and 2011. Data on all readmissions within 3 months of surgery were collected from the Patient registry, Swedish Board of Health and Welfare. For each readmission the highest Clavien-Dindo grade was listed. Results: A total of 4003 patients were included in the LAPPRO trial and, after applying exclusion criteria, 3706 patients remained for analyses. The results showed no statistically significant difference in the overall readmission rates (8.1 vs. 7.1%) or readmission due to major complications (Clavien-Dindo ≥3b, 1.7 vs. 1.9%) between RALP and RRP within 90 days after surgery. Patients subjected to lymph-node dissection (LND) had twice the risk for readmission as men not undergoing LND, irrespective RALP or RRP technique. Blood transfusion was significantly more frequent during and within 30 days of RRP surgery (16 vs. 4%). Abdominal symptoms were more common after RALP. Conclusions: There is a substantial risk for hospital readmission after prostate-cancer surgery, regardless of technique; although major complications are rare. Regardless of surgical technique, attention should be focused on specific types of complications.